CHLORHEXIDINE FOR THE PREVENTION OF OMPHALITIS IN NEONATES WITH A SINGLE DOSE - Dr Allah Nawaz Sultan; Dr Faisal Javed; Dr Nosheen Iftikhar; Dr Shabir Ahmad; Dr Iqbal Ahmad Azhar; Dr Waheed Ahmad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: This study aimed to evaluate the effectiveness of a single application of 4% chlorhexidine in preventing omphalitis in neonates compared to standard cord care practices.Materials and Methods: The study is a randomized control trial which involved 200 neonates with 100 neonates in each of the chlorhexidine group and the control group. Inclusion criteria were live births with an intact umbilical cord at birth while exclusion criteria were neonates with infections and structural anomalies at birth. Therefore, the main focus was on the rate of developing omphalitis during the intended follow-up period.Results: The frequency of omphalitis in the chlorhexidine group was 8 (8%) compared to 24 (24%) for the control group and the relative risk reduction was 66.67% (p < 0.01). Moreover, chlorhexidine was less severe with an average symptom severity score of 2.1 compared to control group’s score of 3.5 on average (p< 0.01).Conclusion: This research establishes that use of 4% chlorhexidine reduces the incidence and severity of omphalitis in the neonate hence implying that should be allowed to be used in the neonatal section.